Knowledge management model based on organizational and motivational mechanisms - M. A. Molodchik; I. A. Esaulova; A. V. Molodchik (Управленческие науки)
Knowledge management is among strategic tasks of a modern company. However, there is a gap in the literature considering the mechanisms of organizational knowledge intensification and its transformation into company competitiveness. The paper presents the knowledge management model based on the vector of proactive employee behavior, which is formed with the help of organizational and motivational mechanisms, including flexible organizational structure, transformational leadership, and a culture of knowledge. According to elaborated model proactive behavior of employees is oriented to knowledge intensiﬁcation and active participation in the processes of organizational development and learning, which in turn determine innovation activities and ﬁnancial performance of a company. The model has been tested using the database of 110 Russian companies that had been participated in the survey in 2019. Empirical results have been estimated in the software smartPLS using the method of structural equations and had conﬁrmed the validity of elaborated knowledge management model. Obtained mediation effects allow making a conclusion about complementarity of the knowledge culture, transformational leadership and ﬂexible organizational structure; therefore, these mechanisms should be implemented simultaneously for the successful transformation of knowledge into a company competitiveness. Also, the practical implication has an empirical evidence of the highest impact of transformational leadership on innovation and ﬁnancial performance, determining this mechanism as a key one for Russian enterprises.